Penerapan Metode Tegangan Harmonisa Ketiga Untuk Proteksi Gangguan Tanah Pada Stator - Ramandana, Ranto; Hasyim Rosma, Iswadi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Short circuit from phase to ground (ground fault) occurring in one of the stator windings of the synchronous generator can cause serious damage to the winding. Therefore, graund fault protection system is required to protect the stator winding of the generator. The method used is to analyze the magnitude of the ratio of the third harmonic voltage of the generator terminal and the generator neutral (V3n/(V3n+V3t)). This method is proven to be able to protect ground fault near neutral point or when low fault current occurred where conventional method is not able to react. To understand that the method is able to protect the fault near the neutral point then the simulation of faults were varied by the variation of fault resistance. It has been found from the result of the simulation that the method has capability to protect 60% stator winding from neutral. The 40% of unprotected winding will be protected by using conventional method in order to have a100% protection performance.Keywords: matlab, stator ground fault, the third harmonic protection